DAMPAK PEMBANGUNAN INDUSTRI PABRIK SEMEN TERHADAP MASYARAKAT SEKITAR DI DESA SOLOG KECAMATAN LOLAK KABUPATEN BOLAANG MONGONDOW - Juriko Nikita Rembet; Martha M. Sendow; Jean F. J. Timban (Sam Ratulangi University, 2018)
This study aims to determine the impact of contruction of cement plant on the surrounding community in Solog Village Lolak District Bolaang Mongondow District. This research was conducted for 5 months from the beginning of December 2017 until May 2018. The data used in this research are primary data and secondary data. Primary data was obtained from interview to 35 respondent. Sampling selection used purposive sampling method. Secondary data was obtained from documents of Solog Village Office. The results of this study indicate that the construction of PT Conch cement factory industry has a positive and negative impact for the community in Solog Village. Positive impacts are the availability of job and business opportunities, increased income and assistance funding for activities in the village of Solog. While the negative impact is the decrease of agricultural land area due to land conversion resulting in reduced agricultural yields and other potential conflicts due to the emergence of social jealousy from some communities/indigenous peoples to the immigrant community in terms of ease of getting a job at PT Conch.*eprm*.